107 COVID 19 - Developing A Second Brain for Axillary Conservation During the Pandemic By Extrapolating Evidence On Technical Trends Of Sentinel Node Staging Of Axilla Into A Streamlined Recommendation. (4th May 2021) - Arif, T; Absar, M S
Abstract: Introduction: Axillary conservation is the way forward after game changing trials like ACOSOG Z0011, surrogate trials like IBCSG, AMAROS, ALMANAC, on-going POSNOC, and newbie ATNEC have decreased the need to fiddle with the axilla. Current standard is the utilisation of double technique with radioisotope and blue dye to decrease false negative rates for true sentinel node retrieval. Method: Literature search on the topic in the last two decades. Results: The search yielded 197 publications which were subjected to a meticulous review. Conclusions: Single agent radioisotope is recommended in palpable and good biology breast tumours. Use of single agent blue dye can be standardised in axillary tail tumours. It is also recommended when isotope mapping is logistically not feasible or during pandemics like COVID 19 where looming infrastructure challenges are prevalent. Dual agent technique should be considered in previously treated breast and axilla, neoadjuvant chemotherapy cohort, bad tumour biology, high BMI and macromastia groups for true nodal retrieval. Optimal number of nodes taken out should not be more than three (n = 3). Lower axillary sampling of not more than 3 nodes is recommended for troubleshooting. Magnetic tracing can be used as an adjunct to either single agent (RI/BD) technique when there is failure to localise the sentinel node.